Construction Industry Training Assessment Framework - Jadallah, Hazem; Friedland, Carol J.; Nahmens, Isabelina; Pecquet, Charles; Berryman, Charles; Zhu, Yimin (Frontiers in Built Environment, 2021)
The construction industry suffers from a lack of structured assessment methods to consistently gauge the efficacy of workforce training programs. To address this issue, this study presents a framework for construction industry training assessment that identifies established practices rooted in evaluation science and developed from a review of archival construction training literature. Inclusion criteria for the evaluated studies are: archival training studies focused on the construction industry workforce and integration of educational theory in training creation or implementation. Literature meeting these criteria are summarized and a case review is presented detailing assessment practices and results. The assessment practices are then synthesized with the Kirkpatrick Model to analyze how closely industry assessment corresponds with established training evaluation standards. The study culminates in a training assessment framework created by integrating practices described in the identified studies, established survey writing practices, and the Kirkpatrick Model. This study found that two-thirds of reviewed literature used surveys, questionnaires, or interviews to assess training efficacy, two studies that used questionnaires to assess training efficacy provided question text , three studies measured learning by administering tests to training participants, one study measured changed behavior as a result of training, and one study measured organizational impact as a result of training.